"Is it True What They Say about Models?": Modelling African American Womanhood On the Eve of the Civil Rights Era - Haidarali, Laila (Atlantis)

(untitled) (Mount Saint Vincent University, 2007)
This paper explores the work of models, modelling agencies, and popular magazines in forging a new iconography of African American womanhood. These raced and gendered images and ideas engaged heterosexual appeal, feminine deportment, and middle-class consumerist status as a strategy for race advancement on the eve of the civil rights era.